2020
DOI: 10.1038/s41746-020-0246-2
|View full text |Cite
|
Sign up to set email alerts
|

Automatic, wearable-based, in-field eating detection approaches for public health research: a scoping review

Abstract: Dietary intake, eating behaviors, and context are important in chronic disease development, yet our ability to accurately assess these in research settings can be limited by biased traditional self-reporting tools. Objective measurement tools, specifically, wearable sensors, present the opportunity to minimize the major limitations of self-reported eating measures by generating supplementary sensor data that can improve the validity of self-report data in naturalistic settings. This scoping review summarizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 81 publications
0
80
0
Order By: Relevance
“…In recent years, wearable devices have played a crucial role in many different applications, including occupational accident prevention, fitness, and medical care, thanks to the ability to combine many low-cost sensors in the same network 4 6 . In the healthcare field, user-friendly wearable devices allow vital signs to be measured and monitored with different granularity levels.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, wearable devices have played a crucial role in many different applications, including occupational accident prevention, fitness, and medical care, thanks to the ability to combine many low-cost sensors in the same network 4 6 . In the healthcare field, user-friendly wearable devices allow vital signs to be measured and monitored with different granularity levels.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent literature survey, Bell et al reported that 33 research studies performed an in-field assessment with a meal detection system [ 14 ]. The in-field assessment entailed participants using the sensor setup in a “free-living” condition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, identifying when individuals eat can be used to infer if individuals are consuming food at regular intervals of time. Recent ubiquitous computing research has shown promise in eating detection, primarily showing various ways to infer when an individual is eating [ 10 - 14 ]. However, dietary patterns of an individual are not exclusively related to their interactions with food.…”
Section: Introductionmentioning
confidence: 99%
“…They are only beginning to be deployed in non-laboratory settings that capture natural behaviors, and developers have been faced with technological challenges and behavioral confounders, such as the hand-tomouth activity involved in smoking or nail biting. Bell and colleagues recently (March 2020) published a review of 33 peer-reviewed journal or conference papers published through December 2019, describing 40 studies that focused on current use of wearable devices and sensors that automatically detect eating activity in free-living research settings [46]. They note that measures for evaluating performance of these devices in the field are highly varied and lack uniformity.…”
Section: Wearable Trackersmentioning
confidence: 99%